Coincidence as a motif of divine intervention in 1 Samuel, 9 - Deist, Ferdinand (Old Testament essays, 1993)
There may be truth in the literary critic conclusion that the role of Yahweh as a visible actor in human history tends to fade in the later writings of the Hebrew Bible. There may, however, also be a purely literary reason for his involvement or non-involvement in human affairs. When a story has to move quickly, Yahweh enters the scene in a 'deus ex machina' fashion. But when a story becomes more reflective and philosophical, Yahweh moves into the background, 'directing affairs as if from a distance, without losing control. This principle of narrative construction is illustrated on the basis of a close reading of 1 Samuel 8-9, focusing more specifically on chapter 9.